Atypical non-progressive pneumonia in goats - Gonçalves, Rosário (2012)
An outbreak of severe respiratory disease in a goat herd was associated with Mycoplasma ovipneumoniae, Mycoplasma arginini, Mannheimia haemolytica and Pasteurella multocida with mortality rates exceeding 20% in kids. Post mortem features in affected kids included severe pleuropneumonia, lung consolidation, large quantities of pleural fluid and pericarditis. This is the first report of atypical proliferative pneumonia in goats in Portugal.